Implementation of an automated inclusion system for the histological analysis of murine tissue samples: A feasibility study in DSS-induced chronic colitis. (19th May 2018) - Cribiù, Fulvia Milena; Burrello, Claudia; Ercoli, Giulia; Garavaglia, Federica; Villanacci, Vincenzo; Caprioli, Flavio; Bosari, Silvano; Facciotti, Federica
Animal models are powerful tools to expand our understanding of human diseases. Histopathological evaluation of murine experimental models is often required to support further research; thus, a more rigorous evaluation of murine histological samples is strongly advocated. Indeed, the overall quality of tissue sections is critical to draw reliable and accurate conclusions. As several methodological variables may reduce the reliability of the pathological analysis, a standardization of the procedural steps required for the processing of histological murine tissues is advisable. Here, we describe a method to standardize the technical procedure from the initial preparation to the paraffin embedding of murine samples. Specifically, we have implemented an automated inclusion system, that is, the SAKURA Tissue-Tek inclusion instrument, which is routinely used for paraffin inclusion of human samples, to process murine specimens of intestinal inflammation. Colitis severity was assessed in chronically Dextran Sodium Sulphate (DSS)–treated mice by cytofluorimetric analysis of colonic cellular infiltrates, expression of inflammatory genes and histopathological analysis of tissue samples, comparing manual and automated tissue preparation systems. We here conclude that implementation of this technique can significantly increase the quality and the reliability of histopathological examination of murine tissues.